Penyelesaian Tindak Pidana Penganiayaan Melalui Diversi - Yuliana, Sri; Asba, Pathillah; Tijjang, Bakhtiar (Jurnal Litigasi Amsir, 2023)
In the implementation of juvenile criminal justice, there is the fact that criminal court proceedings for children have a negative impact on children. This research aims to find out the settlement of criminal cases against children through diversion in the jurisdiction of Sidrap Police. This research uses normative and empirical types of research with qualitative approaches. Data sources use primary legal materials and secondary legal materials. The results of this study show that the settlement of criminal cases against children through diversion in the Sidrap police is the Pre-Diversion Stage, the Diversion Process Stage, and the Diversion Agreement Results Stage. The Diversion process must pay attention to the interests of the victim. The welfare and responsibility of the child. The results of the Diversi agreement can be formed, among others, peace with or without compensation, handover to parents/guardians, participation of educational institutions or LKPS for a maximum of 3 (three) months, or community service.